2018
DOI: 10.1111/plb.12728
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana expressing PbBSMT, a gene encoding a SABATH‐type methyltransferase from the plant pathogenic protist Plasmodiophora brassicae, show leaf chlorosis and altered host susceptibility

Abstract: The plant pathogenic protist Plasmodiophora brassicae causes clubroot disease of Brassicaceae. This biotrophic organism can down-regulate plant defence responses. The previously characterised P. brassicae PbBSMT methyltransferase has substrate specificity for salicylic, benzoic and anthranilic acids. We therefore propose a role for the methylation of SA in attenuating plant defence response in infected roots as a novel strategy for intracellular parasitism. We overexpressed PbBSMT under the control of an induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 50 publications
(126 reference statements)
2
29
0
Order By: Relevance
“…3). These results again confirm findings from previous studies 27,33 , but our results are the first to pinpoint these changes to specific life cycle stages. Notably PbBSMT mRNAs accumulate around the developing resting spores in the sporogenic plasmodia (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…3). These results again confirm findings from previous studies 27,33 , but our results are the first to pinpoint these changes to specific life cycle stages. Notably PbBSMT mRNAs accumulate around the developing resting spores in the sporogenic plasmodia (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…MeSA was specifically emitted from Arabidopsis leaves infected with P. brassicae 33 . Combined with findings from previous studies 27,33,48 , our observations strongly support the role in host defence suppression of PbBSMT, making it a very interesting target for future studies.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We also found a gene model (Phvul.004G023900) that encodes a methyltransferase that impart quantitative resistance to race 503. The role of methyltransferases in plant disease resistance is well documented against an array of plant pathogens ( Yang et al, 2017 ; Wang et al, 2018 ; Bulman et al, 2019 ). Besides Pv04, this study identified a SNP on Pv09 for quantitative resistance against race 503 in gene model Phvul.009G169600 that encodes a zinc finger protein.…”
Section: Discussionmentioning
confidence: 99%
“…Validation of the RNA-seq data through qPCR [77] or ddPCR [78], identification of the subcellular localization of the candidate effector proteins [20] through transient expression or stable transformation [21,79] and identification of the plant proteins interacting with the pathogen effectors are some of the logical next steps towards the identification of P. brassicae effector proteins. The work with pathogen effectors in general is challenging, but the work with intracellular, biotrophic pathogens appears to be even more so, requiring creativity and novel solutions.…”
Section: Discussionmentioning
confidence: 99%